Voimistaminen dis-, mal- ja misinformaation levittämisessä ja sen esiintyminen Suomessa - Kettunen, Teo (2024)
The thesis examines the amplification of dis-, mal- and misinformation in theory and empirically how it occurs in Finland based on theory driven qualitative content analysis. The empirical study focuses on different internet-based publications that possibly could spread dis-, mal- or misinformation. There are only a few of previous studies about the topic and practically non regarding Finland. The thesis defines amplification of dis-, mal- and misinformation as the deliberate use of various methods and of combination of these to willingly spread a false or misleading message, idea or narrative, to disguise its origins and to increase its credibility on one or several communication platforms also exploiting natural human tendency to amplify content that appeals to them. One of the key findings of the thesis is that actors often try to get their message to spread on several different platforms so that a person trying to confirm the false information they encounter would run into the false information also when trying to confirm it from other sources. Regarding Finland all the amplification methods defined in theory based on cases in other countries are also used in Finland similarly to the way they were used in the other cases, which points out the need for further studies of the topic in Finland. A central part of the thesis is the comparison with other disciplines expe-riencing amplification. Especially in communication studies there are studies of very similar topics. Based on this it is possible to conclude that even if the topic of amplification regarding dis-, mal- and misinformation is quite new, it is rather an older phenomenon that has been transferred to a new environment where the advances in technology and communication systems allows it to further evolve in the future and gain new forms.